A Proposal to Apply the Historic Urban Landscape Approach to Reconstruction in the World Heritage Context. (2nd January 2018) - Khalaf, Roha W.
Abstract: Sir Patrick Geddes remarked that a city is a living organism, which experiences birth, growth, maturity, decline, decay and rebirth. It is a palimpsest in the urban landscape, a historic layering of human interventions. Some layers may remain in good physical condition, while others may deteriorate or vanish due to different factors such as ageing, neglect, natural disasters or armed conflicts. The unfortunate destruction of districts and cities, inscribed on the UNESCO List of World Heritage in Danger, is not the end of their wheel of life because new layers can emerge. Some may resemble old ones to meet the claims and needs of contemporary society. This layering process echoes the thinking that underpins the Recommendation on the Historic Urban Landscape (HUL). While the term 'reconstruction' does not appear in the latter, it is implied in Item 20: 'Changes to historic urban areas can also result from sudden disasters and armed conflicts. […] The [HUL] approach may assist in managing and mitigating such impacts'. This paper takes ongoing intellectual discussions and studies on reconstruction in the World Heritage context forward by exploring how this approach may be of assistance. A critical examination of the recurring concept of authenticity is included.